2009
DOI: 10.1186/1471-2164-10-331
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the RpoN regulon in Geobacter sulfurreducens

Abstract: Background: The role of the RNA polymerase sigma factor RpoN in regulation of gene expression in Geobacter sulfurreducens was investigated to better understand transcriptional regulatory networks as part of an effort to develop regulatory modules for genome-scale in silico models, which can predict the physiological responses of Geobacter species during groundwater bioremediation or electricity production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 81 publications
(95 reference statements)
4
58
0
Order By: Relevance
“…For example, the gene GSU1745 that encodes the essential outer membrane porin OmpA 24 was only associated with a s N -dependent promoter. This observation is consistent with the previously failed attempts to generate viable rpoN (s N ) knock-out strains for G. sulfurreducens under multiple growth conditions 14 .…”
supporting
confidence: 80%
See 3 more Smart Citations
“…For example, the gene GSU1745 that encodes the essential outer membrane porin OmpA 24 was only associated with a s N -dependent promoter. This observation is consistent with the previously failed attempts to generate viable rpoN (s N ) knock-out strains for G. sulfurreducens under multiple growth conditions 14 .…”
supporting
confidence: 80%
“…We confirmed many genes previously described to be regulated by s H , such as heat-inducible chaperones (for example, hspA) 13 , or by s N , such as the nitrogenase molybdenum-iron cofactor biosynthesis protein (nifEN) 14 . In addition to nifEN being transcribed from a s N -specific promoter, s N was the only s factor controlling this essential gene for nitrogen fixation.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…FleQ and FlrA activate flagellar genes whose expression is RpoN-dependent, consistent with the fact that EBPs generally promote transcription of RpoN-dependent genes (22,23). It has previously been suggested that the expression of some flagellar genes in G. sulfurreducens may be RpoN-dependent (25,26).…”
mentioning
confidence: 57%